A Study of Overpopulation and Ecological Suicide: How Religion Plays a Role - Dzurriyatin Thoyyibah; Mochammad Maola (Journal of Islamic Studies and Humanities, 2020)
The damage of overpopulation gives a warning toward ecological issue. The massive number of human population could not be defined as an advantage at all, moreover with the imbalance of development and migration. Every human being are consuming and taking space for living. Lessons from many ecological disasters have been occurred across the globe. Some scholars are addressing religion as one of the source toward the ecological crisis. Meanwhile some other are distinguishing between world religion and indigenous religion and accusing world religion as the problem toward ecological crisis, and indigenous religion is a way closer and attach to the nature. This paper will study the overpopulation of human and it’s impact toward ecological suicide. In addition, religion in this context, will be analyzed whether it has a role, either as trigger, booster (religious justification), or solution. By using literature study and descriptive analysis, this paper is presenting the overview of religions role toward ecological crisis to give insight on how to understanding and practicing religion to make sure the demography bonus doesn’t led to overpopulation and gives bad impact toward ecological suicide.